Pokémon. Sword & shield. Volume 3 - Kusaka, Hidenori; Tanzer, Molly (Viz Media, LLC, 2022)
Casey Shield, a hacker who invented the Dynamax Simulator, and Henry Sword, a boy who repairs gear for Pokémon, both dream of entering the Galar region's Gym battles. For Casey, it's a chance to reunite with her lost Pokémon. For Henry, it's an opportunity to search for the legendary Rusted Sword and Rusted Shield. Henry and Casey participate in the Gym Challenge! Henry's skills as a Pokémon Gear Artisan are put to the test as he battles multiple Gym Leaders! Meanwhile, Casey continues to search for her long-lost Pokémon. Are Henry and Casey up to their new tasks?